Exploring Relationships among Test Takers' Behaviors and Performance Using Response Process Data - Sergio Araneda; Dukjae Lee; Jennifer Lewis; Stephen G. Sireci; Jung Aa Moon; Blair Lehman; Burcu Arslan; Madeleine Keehner (MDPI AG, 2022)
Students exhibit many behaviors when responding to items on a computer-based test, but only some of these behaviors are relevant to estimating their proficiencies. In this study, we analyzed data from computer-based math achievement tests administered to elementary school students in grades 3 (ages 8-9) and 4 (ages 9-10). We investigated students' response process data, including the total amount of time they spent on an item, the amount of time they took to first respond to an item, the number of times they "visited" an item and the number of times they changed their responses to items, in order to explore whether these behaviors were related to overall proficiency and whether they differed across item formats and grades. The results indicated a non-linear relationship between the mean number of actions and proficiency, as well as some notable interactions between correctly answering an item, item format, response time, and response time latency. Implications for test construction and future analyses in this area are discussed.